Evidence Types and Trends in Tropical Forest Conservation Literature. (July 2019) - Burivalova, Z.; Miteva, D.; Salafsky, N.; Butler, R.A.; Wilcove, D.S.
Abstract : To improve the likelihood of conservation success, donors, policy makers, nongovernmental organizations (NGOs), and researchers are increasingly interested in making conservation decisions based on scientific evidence. A major challenge in doing so has been the wide variability in the methodological rigor of existing studies. We present a simple framework to classify different types of conservation evidence, which can be used to understand the strengths, weaknesses, and biases in the conservation effectiveness literature. We then apply this framework to evaluate the evidence for the efficacy of four important strategies in tropical forest conservation. Even though there has been an increase in methodologically rigorous studies over time, countries that are globally important in terms of their biodiversity are still heavily under-represented by any type of conservation effectiveness evidence.